Implementasi Undang-Undang Kesehatan: Implikasi Terhadap Kesejahteraan Masyarakat Dan Perspektif Tenaga Kesehatan Di Indonesia - Agustin, Ruli; Syahuri, Taufiqurrohman (Bacarita Law Journal, 2024)
The amendments made to the Health Law Number 17 of 2023 represent Indonesia's commitment to enhancing the welfare of its citizens, particularly in the field of healthcare. A key aspect of this law is to provide broader and more equitable access to higher quality healthcare services for all Indonesian citizens, addressing the shortcomings of previous healthcare legislations. This study aims to analyze the controversies within the healthcare law, examining their impact on societal well-being and assessing the law's implementation within the framework of national development. Employing a juridical-normative research method using a statutory approach, the findings of this research indicate that the amendments introduced in the Health Law Number 17 of 2023, despite creating controversies within the healthcare sector, are aimed at ensuring widespread and equitable access to healthcare services and improving their quality in Indonesia. Hence, the nation's goal of providing welfare in the healthcare sector indirectly relies on the concurrent operation of existing laws, implementation of regulations, and public compliance awareness.